Republic of Equatorial Guinea : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This Selected Issues paper discusses fiscal sustainability and capital expenditures for Equatorial Guinea. The paper formulates a permanent income hypothesis model and estimates it using data on oil revenues from Equatorial Guinea. The first methodology is based on a standard permanent income model, using a 50-year time horizon and real rate of return of 2 percent. The paper then extends the model to incorporate a feedback effect from capital spending to non-oil GDP growth, and shows its implications for fiscal sustainability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet